Cardiovascular Toxicities from Systemic Breast Cancer Therapy - Guo, Shuang; Wong, Serena (Frontiers in Oncology, 2014)
Cardiovascular toxicity is unfortunately a potential short- or long-term sequela of breast cancer therapy. Both conventional chemotherapeutic agents such as anthracyclines as well as newer targeted agents such as trastuzumab can cause varying degrees of cardiac dysfunction. Type I cardiac toxicity is dose-dependent and irreversible, whereas Type II is not dose-dependent and is generally reversible with cessation of the drug. In this review we discuss what is currently known about the cardiovascular effects of systemic breast cancer treatments, with a focus on the putative mechanisms of toxicity, the role of biomarkers, and potential methods of preventing and minimizing cardiovascular complications.